Postgraduate design education and sustainability—An investigation into the current state of higher education and the challenges of educating for sustainability - Delaney, Emelia; Liu, Wei (Frontiers in Sustainability, 2023)
Introduction Sustainability has remained an important issue within academia and industry, with more recent focus on sustainability education to ensure that future generations are equipped with the knowledge to continue and champion sustainable outcomes. The design and innovation industry has been continuously identified as important by academia, for having high impact on the potential sustainability of products and services during their development. However, little research focuses on the pre-professional education of designers and whether they receive an appropriate education on sustainable issues in relation to their industry. Methods This study investigated these issues within the context of United Kingdom-based postgraduate design courses, to determine the current state of sustainability education as well as the impact of government resources and policies on encouraging sustainability education. Courses were identified utilizing online databases and were evaluated using Sterling's model “Levels of Response to Sustainability Education” to understand the current approach to sustainability within design education, including content and pedagogy, offering recommendations for improvement. Results Courses were evaluated against Sterling's model “Levels of Response to Sustainability Education”, which enabled the understanding of the current state of higher education and sustainability education with Postgraduate design courses in the UK. Following this review, a model for upgrading sustainability education is proposed. Discussion Around 80% of the courses identified throughout this study were ranked as “weak” or “very weak” according to Sterling's model, the proposed model highlights several strategies to aid postgraduate design courses to progress to the “strong” level. The framework model focuses on various sustainability themes to be included within postgraduate design education, teaching methods, as well as the inclusion of a dedicated student reflection period to improve and adapt the sustainability teaching.